Artificial intelligence for knowledge management : 5th IFIP WG 12.6 International Workshop, AI4KM 2017, held at IJCAI 2017, Melbourne, VIC, Australia, August 20, 2017, Revised selected papers /: 5th IFIP WG 12.6 International Workshop, AI4KM 2017, held at IJCAI 2017, Melbourne, VIC, Australia, August 20, 2017, Revised selected papers. (2019) - Unknown
No abstract available